Alanine‐(87)‐threonine polymorphism impairs signaling and internalization of the human P2Y11 receptor, when co‐expressed with the P2Y1 receptor. (13th February 2014) - Haas, Michael; Shaaban, Ahmed; Reiser, Georg
Abstract The P2Y11 nucleotide receptor detects high extracellular ATP concentrations. Mutations of the human P2RY11 gene can play a role in brain autoimmune responses, and the P2Y11 receptor alanine‐87‐threonine (A87T) polymorphism has been suggested to affect immune‐system functions. We investigated receptor functionality of the P2Y11A87T mutant using HEK293 and 1321N1 astrocytoma cells. In HEK293 cells, the P2Y11 receptor agonist 3′‐O‐(4‐benzoylbenzoyl)adenosine 5′‐triphosphate (BzATP) was completely inactive in evoking intracellular calcium release while the potency of ATP was reduced. ATP was also less potent in triggering cAMP generation. However, 1321N1 astrocytoma cells, which lack any endogenous P2Y1 receptors, did not display a reduction. Only when 1321N1 cells were co‐transfected with P2Y11A87T and P2Y1 receptors, the calcium responses to the P2Y11 receptor‐specific agonist BzATP were reduced. It is already known that P2Y1 and P2Y11 receptors interact. We thus conclude that the physiological impact of A87T mutation of the P2Y11 receptor derives from detrimental effects on P2Y1–P2Y11 receptor interaction. We additionally investigated alanine‐87‐serine and alanine‐87‐tyrosine P2Y11 receptor mutants. Both mutations rescue the response to BzATP in HEK293 cells, thus ruling out polarity of amino acid‐87 to be the molecular basis for altered receptor characteristics. We further found that the P2Y11A87T receptor shows complete loss of nucleotide‐induced internalization in HEK293 cells. Thus, we demonstrate impaired signaling of the P2Y11 A87T‐mutated receptors when co‐operating with P2Y1 receptors. <boxed-text content-type="graphic" id="jnc12666-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text> The human P2Y11 nucleotide receptor plays key role in immune‐responses in brain and other tissues. We provide evidence for significant functional disturbance of the P2Y11 receptor carrying the Alanine‐87‐Threonine mutation caused by natural polymorphism. This receptor defect is apparent only when co‐expressed with P2Y1 receptors. We found reductions in ligand‐induced calcium and cAMP responses and in nucleotide‐induced receptor internalization / resensitization. Thus, prolonged nucleotide treatments are the basis for the molecular defects of the mutant receptor in diseases.